Exploring Stereospermum colais Derived Ag and TiO₂ nanoparticles: A Comparative Insight into Biomedical Applications - Satyanarayana, Nagamani Thandaga; Nadipinayakanahalli Munikrishnappa, Guruprasad; Kannasandra Ramaiah, Manjula (Journal of Neonatal Surgery, 2025)
Green synthesis of nanoparticles using plant extracts has gained immense interest due to its eco-friendly, cost-effective, and biocompatible approach. This study compares the synthesis, characterization, and biological applications of green-synthesized titanium dioxide (TiO₂) and silver nanoparticles (AgNPs) derived from Stereospermum colais extracts. The nanoparticles were analyzed using various spectroscopic and microscopic techniques, including UV-Vis, FTIR, XRD, SEM-EDX, Raman spectra, DLS, and Zeta potential. Their biological properties, including cytotoxicity, antimicrobial efficacy, and potential anticancer applications, were evaluated using MTT, MIC, DPPH, and RT-PCR assays. Cytotoxicity studies were conducted using MCF-7 (breast cancer) and SHSY5Y (neuroblastoma) cell lines to assess anticancer potential. Statistical tools such as ANOVA, correlation analysis, and regression analysis were employed to compare the biological efficacy of AgNPs and TiO₂ NPs. The findings provide insights into the comparative efficiency of these nanoparticles and highlight their potential applications in biomedical and environmental fields.